(untitled) (Experimental biology, 2016)
The author’s own research and literary data indicate that the plant root system have features hereditarily determined and a number of them parameters (the depth of penetration, intensity branching character of the propagation, intensity formation and development of adventitious roots, lifetime and the mass of roots) have enough strong changing depending from the environment. All of this affect on the area of the absorbing surface, and hence the intensity of the sufficiency of water-supply and absorption of nutrients and ultimately on the biological plant productivity. One of the most important points in the relationship of most species of higher plants with the environment is the relationship of plants with edaphic environment carried out by the root system. Therefore, the functional properties of the root system, and, consequently, the degree of water supply of the overground organs, elements of soil nutrition, plant productivity and stability depend on the nature of growth and development, distribution and from many morphological features of the root system. New notion of root saturation of the soil or any substrate is proposed to introduce in rhizology by authors (Baitulin, Mukhitdinov). Degree of impact and intensity of biological conversion factor of the substrate, the intensity and nature of soil-forming process is largely dependent on this. We can characterize the root saturation as follows: the degree of soil permeated by roots (this total length of roots in a certain volume of soil); ability of contact by roots with soil (surface area of the root this is in a certain volume of soil) and, finally, the root-soil ratio (this is volume root in a certain volume of soil). This clarification of the root saturation of the soil allow more specifically to characterize relationship plants with soil environment.